Suwuk : Construction of the Javanese People's Mindset in Medicine - Kodrat Eko Putro Setiawan; Wahyuningsih Wahyuningsih Wahyuningsih; Dedy Richi Rizaldy; Devi Cintia Kasimbar (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Suwuk is a traditional medicine that still exists in Javanese society, including the Ngawi people. This study aims to describe and explain the Javanese people's mindset about suwuk as a traditional medicine. The method in this research is descriptive qualitative. The subjects in this study were people who were directly involved in the Suwuk procession in the Ngawi Regency, East Java Province. The result of his research is that Suwuk is included in the element of technology. The practice of suwuk is carried out using media and mantras. Community pattern construction: Suwuk still exist and coexist with modern medicine; The emergence of diseases can be caused by two things, namely diseases that can be treated medically and there are diseases that are considered unnatural so that they must be treated through Suwuk. There is a pattern of community treatment that applies from generation to generation and is suggestive. The treatment procedure through Suwuk consists of two stages, namely: first, the stage of diagnosis and selection of the right treatment method; and second, the application of treatment. Diagnosis is basically done through numerology or petungan , intuitive knowledge. While the application of treatment through techniques, among others, through the media and spells.